“Caracterización del mapa de consumo de combustible para un motor de combustión interna de encendido provocado en condiciones reales de funcionamiento” - Borrero Sandoval, Daniela María (2021)
The main objective of the research project is to characterize the specific fuel consumption map of a 2010 Kia Sportage light car. The research is focused on the car's spark ignition engine working under the Otto Cycle. The established model is Beta 2.0 L engine of DOHC type. In this research 10 road tests were carried out, which were executed on the Santo Domingo - Quevedo. During the experimentation, CAN edge1 and the Skywatch GEOS 11 portable multifunction station were used to collect the data required for the study. The CAN edge1 device is an on-board diagnostic instrument that works under the OBDII protocol and delivers specific variables in real time. From the parameters obtained, the air mass flow in kg/s is calculated, since the car does not have a MAF sensor, and then the SFC (Specific Fuel Consumption) is calculated. Once the SFC values have been obtained, we proceed to characterize them in a diagram that is a function of the torque and power established for the car's engine. At the same time, the characteristic curves of the engine generated by the manufacturer under ideal conditions and the diagram obtained through experimentation in the road tests carried out under operating conditions were shown. This diagram allows us to verify that the results remain below the characteristic curve generated by the manufacturer. Keywords: Specific fuel consumption, Engine characteristic curves, Beta II engine, MAF sensor